Optimizing healthcare outcomes and broadening nursing capabilities in digital era: telemedicine transformative impact - Prathiba, P. M.; Umar, Mohammed; C. V., Siji; Irshad Rathore, Mohammed; Geetha, Paramasivam Asari; Karfe, Kashinath; Suhashini; N. R., Deepa (International Journal of Research in Medical Sciences, 2025)
The telemedicine concept brought about a revolution in caring and led to efficient and effective nursing practice. The aforementioned improvements in patient outcomes and the positive advancements in patient care and accessibility were catalysed by the 2020 pandemic. The advent of this patient-centred care under telemedicine has ensured patient access, reduced costs, and encouraged general patient satisfaction. More so, the innovations are felt more in underserved populations, and rural populations recorded appreciable improvement in care pathways with professional access on a hospital proximity basis. Moreover, telemedicine has helped bridge critical gaps in healthcare for so long within the underserved regions. In nursing, telemedicine has maintained workable handover and helped expand safety from viral or bacterial infection chain to mental health and sanity. For example, patient circumstances such as diabetes have seen telemedicine innovations in ways that ensure patients are being monitored in remote places and doctors or nurses update patients simultaneously using modern telemedicine platforms. However, the noted issues have been challenges integrating machine operations with existing hospital setups. The future of telemedicine promises continuous remote caring achievable with real time data entry that will improve patient outcomes and nursing practice. In conclusion, telemedicine provides efficient, effective, and accessible nursing care that centers itself with the patient.